2009
DOI: 10.1017/s0033291709991437
|View full text |Cite
|
Sign up to set email alerts
|

A controlled family study of children with DSM-IV bipolar-I disorder and psychiatric co-morbidity

Abstract: Objective To estimate the spectrum of familial risk for psychopathology in first degree relatives of children with unabridged DSM-IV Bipolar-I Disorder (BP-I). Methods We conducted a blinded, controlled family study using structured diagnostic interviews of 157 children with BP-I probands (N=487 1st degree relatives), 162 ADHD (without BP-I) probands (N=511 1st degree relatives), and 136 healthy control (without ADHD or BP-I) probands (N=411 1st degree relatives). Results The morbid risk (MR) of BP-I disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 47 publications
1
33
0
1
Order By: Relevance
“…These findings are consistent with those identified in adult patients with bipolar MDD (Akiskal et al, 1983;Coryell et al, 1995;Bechdolf et al, 2010) and with the literature on the risk factors for manic switching (Strober and Carlson, 1982;Geller et al, 1994;Biederman et al, 2009). Wozniak et al (2010) previously reported on the significantly increased morbid risk of bipolar disorder in relatives of children with bipolar disorder as compared to relatives of children with only ADHD. This study also found that relatives of children with bipolar disorder have higher rates of psychosis, major, multiple anxiety disorders, substance use disorders, ADHD, and antisocial disorders as compared to relatives of non-bipolar probands.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with those identified in adult patients with bipolar MDD (Akiskal et al, 1983;Coryell et al, 1995;Bechdolf et al, 2010) and with the literature on the risk factors for manic switching (Strober and Carlson, 1982;Geller et al, 1994;Biederman et al, 2009). Wozniak et al (2010) previously reported on the significantly increased morbid risk of bipolar disorder in relatives of children with bipolar disorder as compared to relatives of children with only ADHD. This study also found that relatives of children with bipolar disorder have higher rates of psychosis, major, multiple anxiety disorders, substance use disorders, ADHD, and antisocial disorders as compared to relatives of non-bipolar probands.…”
Section: Discussionsupporting
confidence: 91%
“…Briefly, children with BP-I disorder 6 to 17 years of age of both sexes were assessed at the Clinical and Research Program in Pediatric Psychopharmacology at the Massachusetts General Hospital (Wozniak et al, 2005; Wozniak et al, 2010). Comparators were youth of similar age and sex with and without ADHD, without BP-I disorder (Biederman et al, 1992; Biederman et al, 1999; Biederman et al, 2006a; Biederman et al, 2006b).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 depicts the number of articles identified and their disposition. We reanalyzed data from the Massachusetts General Hospital Pediatric Psychopharmacology Program to allow for stratifying relatives by parents, children, and siblings (29)(30)(31)(32)(33).…”
Section: Methodsmentioning
confidence: 99%